Antibacterial and Antioxidant Activities of Prinsepia utilis Royle Leaf and Seed Extracts. (17th October 2022) - Bagale, Rakshya; Acharya, Srijana; Gupta, Akriti; Chaudhary, Pooja; Chaudhary, Gautam Prasad; Pandey, Jitendra
Abstract : Our study was designed to screen the antibacterial potency of Princepia utilis leaf and seed extract and to measure their antioxidant effects, total phenol content, total flavonoid content, and total carbohydrate content. Collected samples were extracted by cold maceration. Hexane, ethyl acetate, methanol, and distilled water were used as extraction solvents. In the disc diffusion method, P. utilis ethyl acetate leaf extract was most prominent against Staphylococcus epidermis with a zone of inhibition (ZOI) of 13.83 mm. Similarly, methanolic leaf extract was most prominent against Staphylococcus aureus (ZOI-12.33 mm). Furthermore, the methanolic seed extract was most sensitive against Klebsiella pneumoniaee (ZOI-11.66 mm) Escherichia coli (ZOI-9.0 mm). The lowest minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of 0.5 mg/mL and 0.6 mg/mL, respectively, were shown by ethyl acetate leaf extract against S. epidermis . Similarly, the highest values of MIC and MBC, i.e., 20.8 mg/mL and 33.3 mg/mL, respectively, were shown by hexane leaf extract against S. epidermidis. On the other hand, evaluation of antioxidant capacity revealed that ethyl acetate leaf extract showed the maximum antioxidant effect (IC50 : 66.69 μ g/mL). The total flavonoid contents of different extracts were measured in the range of 37 ± 0.74 μ g QE/mg dry extract weight (methanolic seed extract) to 321.84 ± 4.82 μ g QE/mg dry extract weight (hexane seed extract). Likewise, the total polyphenol content ranged from the hexane leaf extract (17.33 ± 0.642 μ g GAE/mg dry extract weight) to ethyl acetate leaf extract (62.56 ± 1.284 μ g GAE/mg dry extract weight). We found a variation in total carbohydrate content in the range of 23.55 ± 1.125 μ g glucose/mg dry extract weight (hexane leaf extract) to 96.63 ± 2.253 μ g glucose/mg dry extract weight (aqueous leaf extract). Overall, this study revealed that leaf and seed extract of P. utilis exhibited noteworthy antibacterial effects against diverse pathogenic microorganisms.